2010
DOI: 10.1016/j.cortex.2009.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Lateralisation of self-esteem: An investigation using a dichotically presented auditory adaptation of the Implicit Association Test

Abstract: Acknowledgement: This study was co-supervised by the first two authors; the order of the last three authors is alphabetical. We thank Drew Fox for valuable discussions and Denika Novello for assistance with data collection. We also acknowledge the helpful comments and suggestions of two anonymous reviewers. AbstractIntroduction: Self-esteem is one of the most prominent and influential constructs in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…RH) and participants' task was to attribute each of these traits either to themselves or to other people. Faster response times for linking good qualities to themselves and negative traits to others were observed when the words were presented through the right-ear [76]. Similarly, rightward errors in the line bisection test, which indicate a relative LH hyperfunctioning, were associated with a tendency of participants to describe themselves as active, dominant, mighty, powerful and strong [77].…”
Section: Introductionmentioning
confidence: 99%
“…RH) and participants' task was to attribute each of these traits either to themselves or to other people. Faster response times for linking good qualities to themselves and negative traits to others were observed when the words were presented through the right-ear [76]. Similarly, rightward errors in the line bisection test, which indicate a relative LH hyperfunctioning, were associated with a tendency of participants to describe themselves as active, dominant, mighty, powerful and strong [77].…”
Section: Introductionmentioning
confidence: 99%
“…Fossati et al (2004) find that the right hemisphere has significant effects on encoding negative words under self-perception evaluation, involving right premotor cortex, right medial prefrontal cortex (dorsal), and right extra-striate cortex, which indicates that negative-evaluation is associated with right hemisphere. McKay et al (2010) conduct an in-depth research on neural representation process of positive self-evaluation using dichotic listening method, which verifies that left hemisphere plays a dominant role in positive self-statements. These findings show that the right and left hemispheres have different self-evaluation neural representations.…”
Section: Discussionmentioning
confidence: 97%
“…Although the original IAT has traditionally been used to measure attitudes (stereotypes/implicit bias) in social psychology (e.g., Gawronski, 2002; Wilson & Scior, 2013), research has shown that adaptations of the IAT paradigm can be used for associations between non‐social categories as well (e.g., flowers/insects and their association with pleasant/unpleasant attributes; Greenwald et al, 1998). Moreover, the IAT works for the auditory domain as well (McKay, Arciuli, Atkinson, Bennett, & Pheils, 2010) and even for the association between auditory and visual domains (Parise & Spence, 2012). This universal applicability encouraged us to use the SIAT as a social variant for investigating associations between vocal and facial stimuli.…”
Section: Methodsmentioning
confidence: 99%